Michel Serres and the Literary Value of Folded Time: A Reading of Innovative Temporalities in Iain Sinclair’s White Chappell Scarlet Tracings and J. G. Ballard’s The Unlimited Dream Company - Dylan Williams (Janeway JS, 2017)
This article explores the representation of time in Iain Sinclair’s White Chappell Scarlet Tracings and J. G. Ballard’s The Unlimited Dream Company and assesses the literary critical potentials of Michel Serres’s concept of folded temporality as a way of approaching them. After briefly introducing the concept of folded time the article shows that the literary texts describe localities at odds with a Kantian linear understanding of time. The article then assesses these ruptured temporalities against Serres’s concept of time through an exploration of the specific functions assigned to intertextuality by the two authors. The authors’ representations of visionary subjectivities are shown to interact with linear and trans-historical temporalities that problematise the use of Serres as a critical framework. Ultimately, the article demonstrates that Michel Serres’s conception of folded time is valuable as a framework for understanding the representation of time in literature. However, its failure to fully address and explain all of the temporal machinations of the two novels demands the image of folded time be subordinated as a tool for existent critical fields, rather than be used to constitute a radical new model of time in literature.
Keywords: political ontology; agency; phenomenology; Hermeneutics; radical democracy